Resolution Of Civil Disputes: Reconciliation Procedures - Esanova Zamira Normurotovna (Peerian Journals Publishing, 2024)
in this article, the role of conciliation procedures in the resolution of civil cases, the classification of conciliation procedures, procedural features, the procedural consequences of using this procedure, including the role of mediation as a conciliation procedure, the methods of achieving mediation, the stages of mediation, and the requirements for a mediation agreement are discussed in this article. -comments, suggestions are included.
Keywords: civil case; settlement agreement; mediation